3,3?-(Pyridine-2,6-diyl)bis(4-allyl-4,5-dihydro-1H-1,2,4-triazole-5-thione) - Cetin, Ahmet; Dincer, Muharrem; Ozdemir, Namik; Dayan, Osman; Cansiz, Ahmet (Int Union Crystallography, 2006)
In the title compound, C15H15N7S2, the asymmetric unit consists of two independent molecules which differ from each other in the orientation of the allyl group. In each molecule, there are two very weak intramolecular C-H center dot center dot center dot N hydrogen bonds. In the crystal structure, the two independent molecules are arranged alternately through N-H center dot center dot center dot S hydrogen-bonded rings to form a molecular chain running along the [12 (1) over bar] direction.